Pengembangan Teknologi Untuk Pengelolaan Lahan Rawa Pasang Surut Berkelanjutan - Ani Susilawati; Erwan Wahyudi; Nurimdah Minsyah (Research Center for Sub-optimal Lands (PUR-PLSO), Universitas Sriwijaya, 2017)
Susilawati et a, 2017. Technology Development for Sustainable Tidal Swamp Land Management. JLSO 6(1):87-94.Tidal land is very potential to be developed as food gardens and agriculture of the future of Indonesia considering (1) productivity is still low, (2) potential land is still wide, (3) indices of plantation (IP) is still low, (4) degraded land potential , (5) the pattern of food production in tidal land is complementary to the pattern of food production in Java, (6) the competition for land use for non-agricultural purposes is relatively low, and (7) the availability of production technology of various commodities. Tidal land is an area whose water availability is affected by the movement of water on the surface of the river due to the movement of the moon, the land is included in the sub-optimal land category, ie the land that has many problems and needs to be overcome in order to provide benefits. The problems are water problems and soil chemical characteristics that have not provided maximum support for agricultural cultivation system. Therefore, priority should be given to technological development that is technically relevant to the characteristics of the land, economically affordable to local farmers, and expected to be in tune with the preferences and socio-cultural of local communities. Two approaches that can be parallel and interactively carried out are [1] optimizing the physical, chemical, and (micro) properties of soil biology along with optimizing the management of water resources to be eff ective and more efficient; and [2] appropriate selection of commodity types and development of adaptively specific varieties for each suboptimal land characteristic.